Mechanical behavior of sustainable building materials using PET waste and industrial by-products - Juárez, C.; Mendoza, J.; González, J.; Rodríguez, J.; Valdez, P. (Rev. Téc. Fac. Ing. Univ. Zulia, 2015)
The building industry is facing the challenge of satisfying a growing demand for housing spaces that can be mitigated by the use of construction materials manufactured with industrial by-products that allow the production of low-cost housing with a low environmental impact. In this research, an alternative building system to manufacture lightweight masonry blocks with polyethylene terephthalate (PET) bottles and fiber-reinforced panels using binary mixture (Portland cement and fly ash), was studied. This building system was tested under compressive and flexural loads until failure. The average design compressive strengths of concrete blocks for w/c ratios of 0.78 and 1.1 were fp = 1.9 and 1.2 MPa respectively, these results were similar to those typical masonry in accordance with the design and construction standards. On the other hand, the flexural strength, the modulus of elasticity and the stiffness on mid span of the fiber-reinforced concrete panels were improved with adding 20% of fly ash to both w/c ratios, mainly at 120 days. The experimental results obtained show that those building elements are viable alternatives with mechanical properties comparable to traditional building systems, besides the reduction of the environmental impact due to the incorporation of industrial waste materials. Â